REVITALISASI KELOMPOK KERJA GURU UNTUK PENINGKATAN KOMPETENSI PROFESIONAL GURU DI TK NEGERI PEMBINA CENTEH KOTA BANDUNG - Iwa Budiana; Nanang Warhdana; Ujang Cepi Berlian (FASTABIQ: JURNAL STUDI ISLAM, 2021)
The competence of a teacher is very important. One of these steps is to form and develop a Teacher Working Group (KKG). At the Centeh Kindergarten School in Bandung, the presence of the KKG is very important for improving the competence of teachers in fostering planning, learning processes, learning methods, and solving problems in the education of kindergarten children. So the mastery of educators in teaching materials and learning methods is an important issue that the KKG pays attention to. The purpose of the study was to understand (1) the process of increasing teacher competence in mastering teaching materials at the Pembina Centeh State Kindergarten School in Bandung City through the Teacher Work Group (KKG), (2) the success of KKG revitalization in Centeh State Kindergarten Schools in Bandung, in overcoming problems -problems that arise in the teaching and learning process. The research method uses a qualitative method with a case study approach. The results of the study, (1) Revitalization of the Teacher Working Group (KKG) in TK Centeh is a process of increasing understanding and competence for teachers in managing teaching materials so that they can maximize the potential of each teacher. students (2) The success of the KKG revitalization program in internal institutions as a forum for teacher professional development has shown an increase in their competence. The competence of teachers is formed so as to create an effective teaching and learning process in the classroom. Keywords : competencies; revitalitation; subject matersAbstrakKompetensi guru penting sekali dalam Pendidikan anak sekolah TK. Untuk itulah perlu peningkatan kompetensi guru. Salahsatunya dengan membentuk dan mengembangkan Kelompok Kerja Guru (KKG). Di Sekolah TK Centeh kota Bandung kehadiran KKG berperan dalam peningkatan kompetensi guru-guru dalam perencanakan, proses pembelajaran, metode pembelajaran, dan memecahkan permasalahan dalam Pendidikan. Tujuan Penelitian, untuk memahami(1) proses peningkatkan kompetensi guru dalam penguasaan materi ajar di sekolah TK Negeri Pembina Centeh Kota Bandung melalui Kelompok Kerj Guru (KKG), (2) Keberhasilan revitalisasi KKG di Sekolah Sekolah TK Negeri Centeh kota Bandung, dalam mengatasi persoalan-persoalan yang muncul dalam proses belajar mengajar. Metode penelitian, menggunakan pendekatan studi kasus. Hasil Penelitian,(1) Revitalisasi Kelompok Kerja Guru (KKG) di TK Centeh merupakan proses peningkatan pemahaman dan kompetensi bagi guru-guru dalam mengelola materi ajar sehingga dapat memaksimalkan potensi setiap anak didik (2) Keberhasilan program revitalisasi KKG di internal menunjukan peningkatan komptenesi guru sehingga menciptakan proses belajar mengajar yang efektif di kelas.Kata Kunci : kompetensi; revitalisasi; materi ajar